THE EFFECT OF LIQUIDITY , GROWTH, PROFITABILITY, AND COMPANY SIZE ON CAPITAL STRUCTURE IN CONSUMER GOODS COMPANIES ON THE INDONESIA STOCK EXCHANGE FOR THE 2016-2020 - Syifa Sonia Putri; Miswanto Miswanto (Jurnal Ekonomi, 2023)
This study aims to examine whether there is an effect of liquidity, growth, profitability, company size on the capital structure of consumer goods companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. In this study, the population used was consumer goods companies listed on the IDX for the 2016-2020 period. The selection of samples was carried out using purposive sampling and obtained 42 companies as samples. The analytical method used in this research is by using multiple regression analysis model with panel data. The results showed that liquidity and profitability had a significant and negative effect on capital structure. Meanwhile, company size and growth have a significant and positive effect on capital structure.